Paving the way for social touch at a distance: Sonifying tactile interactions and their underlying emotions - Alexandra de Lagarde; Catherine Pelachaud; Louise P. Kirsch; Malika Auvray (Proceedings of the National Academy of Sciences, 2025)
Social touch is crucial for human well-being, as a lack of tactile interactions increases anxiety, loneliness, and need for social support. To address the detrimental effects of social isolation, we build on cutting-edge research on social touch and movement sonification to investigate whether social tactile gestures could be recognized through sounds, a sensory channel giving access to remote information. Four online experiments investigated participants’ perception of auditory stimuli that were recorded with our “audio-touch” sonification technique, which captures the sounds of touch. In the first experiment, participants correctly categorized sonified skin-on-skin tactile gestures (i.e., stroking, rubbing, tapping, hitting). In the second experiment, the audio-touch sample consisted of the sonification of six socio-emotional intentions conveyed through touch (i.e., anger, attention, fear, joy, love, sympathy). Participants categorized above chance the socio-emotional intentions of skin-on-skin touches converted into sounds and coherently rated their valence. In two additional experiments, the surface involved in the touches (either skin or plastic) was shown to influence participants’ recognition of sonified gestures and socio-emotional intentions. Thus, our research unveils that specific information about social touch (i.e., gesture, emotions, and surface) can be recognized through sounds, when they are obtained with our specific sonifying methodology. This shows significant promise for providing remote access, through the auditory channel, to meaningful social touch interactions.